Geoaccumulation and distribution of heavy metals in the urban river sediment - Shafie, Nur Aliaa; Aris, Ahmad Zaharin; Haris, Hazzeman (Elsevier, 2014)
Current study presents the application of chemometric techniques to comprehend the interrelations among sediment variables whilst identifying the possible pollution source at Langat River, Malaysia. Surface sediment samples (0-10 cm) were collected at 22 sampling stations and analyzed for total metals (48Cd, 29Cu, 30Zn, 82Pb), pH, redox potential (Eh), salinity, electrical conductivity (EC), loss on ignition (LOI) and cation exchange capacity (CEC). The principal component analysis (PCA) scrutinized the origin of environmental pollution by various anthropogenic and natural activities: four principal components were obtained with 86.34% (5 cm) and 88.34% (10 cm). Standard, forward and backward stepwise discriminant analysis effectively discriminate 2 variables (84.06%) indicating high variation of heavy metals accumulation at both depth. The cluster analysis accounted for high input of Zn and Pb at LA8, LA 10, LA 11 and LA 12 that mergers three (5 cm) and four (10 cm) into clusters. This is consistent with the contamination factor (Cf) that shows high Cd (LA 1) and Pb (LA 7, LA 8, LA 10, LA 11 and LA 12) contaminations at 5cm. These indicate that Pb and Zn are the most bioavailable metals in the sediment with significant positive linear relationship at both sediment depths. Therefore, this approach is a good indication of environmental pollution status that transfers new findings on the assessment of heavy metals by interpreting large complex datasets and predicting the fate of heavy metals in the sediment.